2012
DOI: 10.1364/oe.20.025681
|View full text |Cite
|
Sign up to set email alerts
|

Optical forces on Mie particles in an Airy evanescent field

Abstract: Using vector potential and spectrum representation, we derive the expressions of the Airy evanescent field existed at the interface. Utilizing these expressions and the Arbitrary Beam Theory, the optical forces exerted on a Mie dielectric particle in the Airy evanescent field were theoretically investigated in detail. Numerical results show that the optical forces exhibit strong oscillations which are corresponding to the distributions of the evanescent field. With the increasing the size of particle radius, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…If the imaginary part increases further, (e.g. for nickel, n 3 = 1.5 + 3.1i), the oscillations would disappear by strong absorptions [22]. With a transmitted distance of d = 2.1a shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…If the imaginary part increases further, (e.g. for nickel, n 3 = 1.5 + 3.1i), the oscillations would disappear by strong absorptions [22]. With a transmitted distance of d = 2.1a shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…A. V. Novitsky et al analyzed the dynamics of nonparaxial Airy beams which show the role of evanescent waves [21]. And we have investigated the optical forces exerted on a Mie particle in the Airy evanescent field theoretically [22]. Here, we present a systematic study on the MDRs of the optical forces for a particle illuminated by an Airy beam passes through the interface with respect to the electric field distribution inside the particle which reflects the motions of the internal wave.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Meanwhile, bottle beams [12] and elegant Hermitecosine-Gaussian beams [13] could be used to simultaneously trap two types of particles with refraction index higher or lower than the ambient. In addition, the trapping characteristics of other beams, such as radially polarized beams [14][15][16], vortex beams [17,18], Airy beams [19][20][21], and coherent and partially coherent beams [22][23][24], have also been explored. In all the studies, it is found that the radiation forces are closely related to the initial beam characteristics, such as the coherence, polarization, and spatial profile.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, little quantitative study has been done on the dynamics of optically driven particles near a surface. In studies introducing new schemes to optically manipulate matter, the particle's response function is often ignored (11,12,(26)(27)(28)(29).…”
mentioning
confidence: 99%